Minnesota Juvenile Court Records, 1984-1987 ([Verlag nicht ermittelbar], 1990)
This data collection provides information on the disposition of juvenile court cases (delinquency, status and dependency) in the state of Minnesota. Data are included on all cases petitioned before the juvenile courts and supply information on sex, race, and birth date of juveniles, court referral date, major allegation, number of law violations, number of prior referrals, detention status, court action, and placement status.